2013
DOI: 10.1016/s0140-6736(13)61645-1
|View full text |Cite
|
Sign up to set email alerts
|

Dextrose gel for neonatal hypoglycaemia (the Sugar Babies Study): a randomised, double-blind, placebo-controlled trial

Abstract: BackgroundNeonatal hypoglycemia is common and a preventable cause of brain damage.Dextrose gel is used to reverse hypoglycemia in diabetics. However, there is little evidence for its use in babies. MethodWe enrolled 514 babies 35 to 42 weeks' gestation, < 48 hours, and at risk of hypoglycemia, to a randomized, double-blind placebo controlled trial to determine whether 40% dextrose gel massaged into the buccal mucosa is more effective than feeding alone in reversing hypoglycemia. Hypoglycemic babies were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
192
1
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(221 citation statements)
references
References 25 publications
6
192
1
16
Order By: Relevance
“…However, it could be discussed that neonatal hypoglycaemia in our patients might have been unrelated to MCADD. Neonatal hypoglycaemia affects 5-15% of otherwise healthy newborns (Harris et al 2013). Patient 17 showed ketotic hypoglycaemia, which is not typical for MCADD, but has been reported in a relevant number of MCADD patients before (Iafolla et al 1994).…”
Section: Clinical Phenotypementioning
confidence: 81%
“…However, it could be discussed that neonatal hypoglycaemia in our patients might have been unrelated to MCADD. Neonatal hypoglycaemia affects 5-15% of otherwise healthy newborns (Harris et al 2013). Patient 17 showed ketotic hypoglycaemia, which is not typical for MCADD, but has been reported in a relevant number of MCADD patients before (Iafolla et al 1994).…”
Section: Clinical Phenotypementioning
confidence: 81%
“…[11][12][13][14][15] Hypoglycemia has been extensively reported to have important influence on the outcome of very ill patients, both children and adults. 1,16,17 In Africa, its prevalence among pediatric admissions has been estimated to range between 1.8% and 7.3%.…”
Section: Introductionmentioning
confidence: 99%
“…When there are complete stock-outs of dextrose infusions, health workers reported that they dissolve sugar in water and give it to the child orally. Sublingual administration was not mentioned, though absorption is faster than via the oral route [24], and the use of sublingual 40% dextrose gel rubbed into the oral mucosa has been demonstrated to be comparable to intravenous dextrose in neonatal hypoglycaemia in a high-income setting [25]. The role of sublingual glucose in acutely sick children with confirmed hypoglycaemia showed promising results in a pilot randomized controlled trial [26].…”
Section: Discussionmentioning
confidence: 99%